Inhibitory activity of varronia curassavica and mikania laevigata fractions against pathogens associated with persistent dental infections - Massunari, Loiane [UNESP]; Souza, Amanda C. A. [UNESP]; Domingues, Paula F. K. [UNESP]; Scardelato, Juhan A. [UNESP]; Sacramento, Luis V. S. [UNESP]; Dezan-Junior, Eloi [UNESP]; Duque, Cristiane [UNESP] (Editora Cubo, 2020)
Herbal medicines have been studied as potential antimicrobial agents, emerging as treatments against oral diseases. The current study evaluated the antimicrobial activity of the crude extract and fractions of Mikania laevigata Schultz Bip. ex Baker (ML) and Varronia curassavica Jacq (VC) against oral pathogens associated with persistent dental root infections, under planktonic and biofilm conditions. Minimal inhibitory concentrations and minimal bactericidal/fungicidal concentrations were determined for the ML and VC fractions/extracts against Enterococcus faecalis, Actinomyces israelii, Pseudomonas aeruginosa, and Candida albicans using the microdilution method. The best results were chosen for subsequent biofilm assays. All tested ML and VC extracts/fractions demonstrated inhibitory activity against E. faecalis and A. israelii. The ML ethyl acetate fraction affected the growth of all microorganisms tested. C. albicans and P. aeruginosa were not affected by any VC extract/fractions. The ML ethyl acetate fraction eliminated E. faecalis, A.israelii, and P. aeruginosa biofilms after 24h. A similar result was observed for ML crude hydroethanolic extract and its hexane fraction for A. israelii. The VC hexane fraction was able to eliminate A. israelli biofilms. None of the tested extracts or fractions eliminated C. albicans biofilm. The Mikania laevigata ethyl acetate fraction is an efficient antimicrobial agent against oral pathogens and could be indicated for the treatment of persistent dental infections.
Keywords: Antimicrobial Activity; Phytotherapy; Plant Extracts